The metallochaperone Atox1 plays a critical role in perinatal copper homeostasis - Hamza, Iqbal (The National Academy of Sciences, 2001)
Copper plays a fundamental role in the biochemistry of all aerobic organisms. The delivery of this metal to specific intracellular targets is mediated by metallochaperones. To elucidate the role of the metallochaperone Atox1, we analyzed mice with a disruption of the Atox1 locus. Atox1(−/−) mice failed to thrive immediately after birth, with 45% of pups dying before weaning. Surviving animals exhibited growth failure, skin laxity, hypopigmentation, and seizures because of perinatal copper deficiency. Maternal Atox1 deficiency markedly increased the severity of Atox1(−/−) phenotype, resulting in increased perinatal mortality as well as severe growth retardation and congenital malformations among surviving Atox1(−/−) progeny. Furthermore, Atox1-deficient cells accumulated high levels of intracellular copper, and metabolic studies indicated that this defect was because of impaired cellular copper efflux. Taken together, these data reveal a direct role for Atox1 in trafficking of intracellular copper to the secretory pathway of mammalian cells and demonstrate that this metallochaperone plays a critical role in perinatal copper homeostasis.